Comparing the surgical timelines of military and civilians traumatic lower limb amputations. (March 2016) - Staruch, R.M.T.; Jackson, P.C.; Hodson, J.; Yim, G.; Foster, M.A.; Cubison, T.; Jeffery, S.L.A.
Abstract: The care and challenges of injured service have been well documented in the literature from a variety of specialities. The aim of this study was to analyse the surgical timelines of military and civilian traumatic amputees and compare the surgical and resuscitative interventions. A retrospective review of patient notes was undertaken. Military patients were identified from the Joint Theatre Trauma Registry (JTTR) in 2009. Civilian patients were identified using the hospital informatics database. Patient demographics, treatment timelines as well as surgical and critical care interventions were reviewed. In total 71 military patients sustained traumatic amputations within this time period. This represented 11% of the total injury demographic in 2009. Excluding upper limb amputees 46 patients sustained lower extremity amputations. These were investigated further. In total 21 civilian patients were identified in a 7-year period. Analysis revealed there was a statistically significant difference between patient age, ITU length of stay, blood products used and number of surgical procedures between military and civilian traumatic amputees. This study identified that military patients were treated for longer in critical care and required more surgical interventions for their amputations. Despite this, their time to stump closure and length of stay were not statistically different compared to civilian patients. Such observations reflect the importance of an Orthoplastic approach, as well as daily surgical theatre co-ordination and weekly multi-disciplinary meetings in providing optimal care for these complex patients. This study reports the epidemiological observed differences between two lower limb trauma groups. Highlights: There are different population characteristics between civilian and military traumatic amputees. There was no significant difference in hospital in-patient length of stay between groups. An Orthoplastic approach to this injury group is crucial to optimal management. Daily surgical co-ordination prompts optimal operative planning and treatment. A weekly multidisciplinary planning meeting optimizes the treatment and timelines for these complex patients.